Real-Time Measurement of Ocular Wavefront Aberrations in Symptomatic Subjects - Franco, Sandra; Gomes, Jessica (BioMed research international, 2018)
The purpose of this work was to study the real-time changes of the optical properties of the eye with accommodation in subjects with symptoms of accommodative disorders. From ocular aberrations, it is possible to compute several parameters like the response and lag of accommodation. The ocular aberrations were measured in 4 subjects, with different accommodative disorders, during several cycles of accommodation/disaccommodation and for different accommodative stimuli. The measurement was done continuously and in real time during different accommodative stimuli. It was possible to see the changes in accommodative response during the several stimuli of accommodation. Subjects with accommodative disorders showed different accommodative responses. The use of wavefront ocular aberrations can be a tool to diagnose accommodative disorders. In some subjects with complaints, this method showed irregularities even when the results of the usual clinical exams were normal.